Impact of a program of induced stress therapy on the motor and functional recovery of the upper limb of hemiplegic patients in Kinshasa, Democratic Republic of Congo - Bofosa, Teddy; Kam, Eric; Njimbu, François; Mpefi, Ponce; Kayembe, Tharcis; Miangindula, Betty (Journal of Surgery and Medicine, 2018)
Aim: Stroke is a major cause of disability. As a result of rehabilitation, 80% of hemiplegic patients recover in particular, whereas only 28% to 57% recover the grip. Aim of this study is to evaluate the effects of induced stress therapy on motor and functional recovery of the hemiplegic upper limb, to compare the pace of recovery and upper limb autonomy between hemiplegics subjected to induced stress therapy and not subject to induced stress therapy and evaluate the impact of this therapy in the prevention of upper limb neuromuscular complications and disorders. Methods: This is an interventional study conducted in 30 hemiplegic vascular patients followed at the University Clinics of Kinshasa and at the General Reference Hospital of Kinshasa for 6 months. The pace of recovery was evaluated by the motor index of Demeurisse. We used Pearson’s chi - square to compare the results. The significance level was considered for the value of p≤0.05. Results: The mean age of these patients was 57.5 ± 10.5 years, with a male predominance (63.3%). The majority of these patients were civil servants (23.3%), traders (16.7%) and teachers (16.7%), trades making frequent use of the upper limb. After 6 months of re-education, there was no significant increase in tone in patients undergoing stress-induced therapy (p = 0.34), whereas, for the comparison group, the increase in tone was very significant (p = 0.01); a very significant improvement in motor function (p = 0.000) was observed for the group of induced stress therapy, and significant (p = 0.05) for the comparison group. The progression of pain was good for the group of induced stress therapy (p = 0.02), and negative for patients not subjected to induced stress therapy (p = 0.5). Conclusion: In the course of this study, it was found that induced stress therapy is effective in the functional recovery and prevention of neuro-motor disorders of the upper limb of the vascular hemiplegic.